Positive end expiratory pressure and respiratory system resistance between self-inflating bag and T-piece resuscitator in a cadaveric piglet lung model - Shah, Dharmesh; Tracy, Mark; Hinder, Murray; Badawi, Nadia (Frontiers in Pediatrics, 2022)
Introduction In neonatal resuscitation, T-piece resuscitator (TPR) are used widely, but the evidence is limited for their use in infants born at term gestation. The aim of this study was to compare the delivered positive end expiratory pressure (PEEP) and respiratory system resistance (Rrs) using TPR and self-inflating bag (SIB) in a cadaveric piglet model. Methods Cadaveric newborn piglets were tracheotomised, intubated (cuffed tube) and leak tested. Static lung compliance was measured. Positive pressure ventilation was applied by TPR and SIB in a randomized sequence with varying, inflations per minute (40, 60 and 80/min) and peak inspiratory pressures (18 and 30 cmH2O). PEEP was constant at 5 cmH2O. The lungs were washed with saline and static lung compliance was re-measured; ventilation sequences were repeated. Lung inflation data for the respiratory mechanics were measured using a respiratory function monitor and digitally recorded for both pre and post-lung wash inflation sequences. A paired sample t-test was used to compare the mean and standard deviation. Results The mean difference in PEEP (TPR vs SIB) was statistically significant at higher inflation rates of 60 and 80 bpm. At normal lung compliance, mean difference was 1.231 (p = 0.000) and 2.099 (p = 0.000) with PIP of 18 cmH2O and 30 cmH2O respectively. Significantly higher Rrs were observed when using a TPR with higher inflation rates of 60 and 80 bpm at varying lung compliance. Conclusions TPR is associated with significantly higher PEEP in a compliant lung model, which is probably related to the resistance of the TPR circuit. The effect of inadvertent PEEP on lung mechanics and hemodynamics need to be examined in humans. Further studies are needed to assess devices used to provide PEEP (TPR, SIB with PEEP valve, Anaesthetic bag with flow valve) during resuscitation of the newborn.